2015
DOI: 10.1007/s12016-015-8525-4
|View full text |Cite
|
Sign up to set email alerts
|

The Eosinophil in Infection

Abstract: First described by Paul Ehrlich in 1879, who noted its characteristic staining by acidophilic dyes, for many years, the eosinophil was considered to be an end-effector cell associated with helminth infections and a cause of tissue damage. Over the past 30 years, research has helped to elucidate the complexity of the eosinophil's function and establish its role in host defense and immunity. Eosinophils express an array of ligand receptors which play a role in cell growth, adhesion, chemotaxis, degranulation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
149
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(154 citation statements)
references
References 59 publications
0
149
1
4
Order By: Relevance
“…The higher number of eosinophils suggest sensitization of cellular response to infecting larvae [35]. Previous and updated works on the topic suggest that eosinophilia during helminths infections plays a critical role in providing protective immunity [36,37]. Results from various studies have shown that antigens of developmental stages in parasites are very important for early immunodiagnostics.…”
Section: Mechanisms For Immune Regulation In Gut In Parasitic Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher number of eosinophils suggest sensitization of cellular response to infecting larvae [35]. Previous and updated works on the topic suggest that eosinophilia during helminths infections plays a critical role in providing protective immunity [36,37]. Results from various studies have shown that antigens of developmental stages in parasites are very important for early immunodiagnostics.…”
Section: Mechanisms For Immune Regulation In Gut In Parasitic Managementmentioning
confidence: 99%
“…After a concerted effect on the Th3 cells, they show crosstalk signaling that activated Mast cells, eosinophils and release of various cytokines [48,49]. Presently, presence of early eosinophils is characterized with proinflammatory granulocyte that plays a key role in protection against parasitic invasion [36]. This creates a mainstay for the protective immune response to parasites as well as to allergic diseases [29].…”
Section: Mechanisms For Immune Regulation In Gut In Parasitic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils are initiator and effector cells of Th2-mediated immunity (Ravin and Loy, 2016). They are associated with key components of inflammation in a variety of chronic diseases affecting the airways (Eng and DeFelice, 2016), heart (Séguéla et al, 2015) and gastrointestinal system (Hogan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with key components of inflammation in a variety of chronic diseases affecting the airways (Eng and DeFelice, 2016), heart (Séguéla et al, 2015) and gastrointestinal system (Hogan et al, 2013). Eosinophils are characterized by secretory granules that contain multiple cytotoxic proteins (Ravin and Loy, 2016). Additionally, eosinophils produce reactive oxygen metabolites, lipid mediators and cytokines, all of which are capable of causing severe host tissue damage in eosinophilic inflammation (Barnes, 2011).…”
Section: Introductionmentioning
confidence: 99%